Application practices of frameworks in enterprise architecture: A Systematic literature review - Llosa-Yépez, Luis Armando; Felipe-Bravo, Gaby Mónica; Ramírez-Calderón, Luis Enrique (LACCEI, 2025)
This systematic review evaluates the application of frameworks in enterprise architecture between 2021 and 2025, with the aim of identifying common practices, frameworks used, associated methodologies, and outcomes obtained across various sectors. Following the PRISMA approach and a structured search in Scopus, 31 qualitative and quantitative studies were selected using PIO criteria. The findings reveal that TOGAF was the most widely adopted framework, often combined with methodologies such as SOSTAC, ITIL, and DevOps. The most frequently used indicators included models such as TAM and DeLone–McLean, along with technical metrics like latency and traceability. Most studies focused on the public, educational, and industrial sectors. Although improvements in planning, institutional participation, and operational efficiency were reported, a lack of long-term impact evaluations was identified.